Transformational Community Engaged Research: Our Enriching Domain - C, Sunitha Srinivas; RH, Shobha Rani (Indian Journal of Pharmacy Practice)
As one of the lands of contrast, a key element of disparity is seen in the Indian health sector. While health outcomes improves on one side and a flourishing medical tourism with highly specialised professionals and excellent health care facilities are available for those who can afford it; on the other hand, a large number of people dependent on the over-stretched public health sector, end up with one of the highest out-of-pocket medical expenses in the world. This triggers a vicious cycle that further accentuates poverty which handicaps development of individuals, families and the nation. A complex set of multifaceted issues ranging from suboptimal resource allocation to lack of adequate health care professionals; from gender disparity to other social determinants of health results in inequitable curative, preventive and rehabilitative health care for a large proportion of our population. Our field of Pharmacy Practice research is one of the best fits in responding to the challenges of our health inequity. When the efforts of Transformative Community Engaged Research (TCER) is focussed on health empowerment by accelerating health promotion and disease prevention while continuing with the traditional approaches, it could positively address the health equality issues of the vastly ill-resourced and underserved population. As a way of improving public health based on collaborative partnerships with various communities – schools, anganwadi workers, women self-help groups and Non- Government Organisations, among others, we are in an excellent position to build capacity of the next generation of decision makers - our Pharm.D and Pharmacy Practice graduates. It becomes feasible to initiate synergistic collaborations while managing our double burden of Communicable and Non-Communicable Diseases, when we utilise ethical research practices in our communityfocussed TCER.